2018
DOI: 10.1124/jpet.118.254029
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Dependent Disruption of Adiponectin-Connexin43 Signaling Underlies Exacerbated Myocardial Dysfunction in Diabetic Female Rats

Abstract: Women are diagnosed with type 2 diabetes (T2DM) at an increasing rate, and there is renewed interest in estrogen (E2) replacement therapy (ERT). It remains unknown if E2 contributes to the greater susceptibility of women to diabetes‐evoked myocardial dysfunction. In diabetic men and male animals, the formation of connexin43 (Cx43) hemichannels, at the expense of the physiological Cx43‐based gap junction domain, underlies myocardial dysfunctions. While Cx43 constitutes a promising therapeutic target for cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Mugisho et al demonstrated that the inhibition of Cx43 could improve diabetic retinopathy. Furthermore, malfunctioning cardiac Cx43 signaling was found to play an important role in myocardial dysfunction in diabetic subjects, and the up-regulation of Cx43 in glomerular mesangial cells and diabetic mice was shown to ameliorate experimental diabetes-induced renal oxidative stress and fibronectin (27,28). For the first time, our research team clarified that Cx43 in hyperglycemia could induce monocyte-endothelial adhesion.…”
Section: Discussionmentioning
confidence: 94%
“…Mugisho et al demonstrated that the inhibition of Cx43 could improve diabetic retinopathy. Furthermore, malfunctioning cardiac Cx43 signaling was found to play an important role in myocardial dysfunction in diabetic subjects, and the up-regulation of Cx43 in glomerular mesangial cells and diabetic mice was shown to ameliorate experimental diabetes-induced renal oxidative stress and fibronectin (27,28). For the first time, our research team clarified that Cx43 in hyperglycemia could induce monocyte-endothelial adhesion.…”
Section: Discussionmentioning
confidence: 94%
“…In an attempt to investigate HFpEF, several animal models have been used including the bilateral oophorectomy (OVX) in rats, which provides a valuable model of hypertrophy and HF and allows the investigation of the role of estrogen-induced cardioprotection [ 30 ]. Comorbidities associated with female aging were evaluated in the OVX model which was also been linked to high blood pressure [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], volume overload [ 40 , 41 ], metabolic syndrome [ 42 , 43 , 44 ], type 2 diabetes (T2DM) [ 45 , 46 , 47 , 48 , 49 ] and stress [ 25 , 50 , 51 ].…”
Section: Mechanism Of Menopause-induced Hfpef and Targets For Treatmentmentioning
confidence: 99%
“…E2 exacerbates myocardial dysfunction in ZDF rats by disrupting adiponectin signaling at cardiac level. In part, through the reduction of connexin-43 and phosphorylated survival molecules, ERK1/2 and phosphorylated AKT regulation in the heart [ 45 ], activation of pro-inflammatory pathways in the paraventricular nucleus occurs through the upregulation of ERα/ERβ receptors and adenosine A1/A2a receptors [ 49 ]. E2 paradoxically transforms into a pro-inflammatory hormone in the presence of oxidative stress [ 79 ], such as that induced by diabetes and obesity [ 80 ].…”
Section: Mechanism Of Menopause-induced Hfpef and Targets For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, depressed mechanical forces in atrophied heart may prevent abnormal Cx43 topology and contribute to a decreased susceptibility to developing malignant cardiac arrhythmia. In contrast, the accelerated disruption of cardiac adiponectin-Cx43 signalling is a molecular mechanism for exacerbated cardiac dysfunction and pro-arrhythmias in type-2 diabetic females [ 130 ].…”
Section: Characteristic and Mechanisms Underlying Atrophic And “Antia...mentioning
confidence: 99%